IDENTIFIKASI DAN PREVALENSI CACING ENDOPARASIT PADA IKAN LAYANG DELES (Decapterus macrosoma) DI PELABUHAN PERIKANAN NUSANTARA BRONDONG, LAMONGAN - Fahdi Putra Utama; Kismiyati .; Gunanti Mahasri; Putri Desi Wulansari (Jurnal Akuakultur Rawa Indonesia, 2018)
ABSTRACT                The High Interest of public to Marine fish, create more demand of Slander Scad (Decapterus macrosoma). Slander Scad is one commodity that has economic value and high nutritional content. The Slander Scad is obtained from the catch of fishermen in the Nusantara Fishery Port Brondong, Lamongan. Fish that caught from the wild is likely to get a disease caused by infection of the endoparasites.worm.           The parasites that infect Slander scad probably caused by environmental factors that could decrease immune system, causing the fish easily infected by endoparasites worm such as Anisakis. This parasite is zoonotic and can infect humans, therefore, to identify and prevalence for humans who consume fish can manage properly. The purpose of this study was to identify the species of endoparasite worms that infect Slander Scad (D. Macrosoma) in Nusantara Fishery Port of Brondong, Lamongan. The research method is using a survey method through sampling at locations directly. 75 samples of Slander Scad were examined. The main parameters observed in this study are to observe the species and the prevalence of endoparasitic worm that infected Slander scad. The result of the identification of endoparasite that infected Slander Scad were analyzed descriptively and presented in the form of figures and tables. The results showed the presence of the third-stage Anisakis simplex larvae that infect the Slander Scad in the liver, intestines, gonads, muscles in the abdominal side, in the Nusantara Fishery Port of Brondong Lamongan, East Java with a total prevalence of Anisakis simplex worm was 42.67%.                               Keywords: Slander Scad, Prevalence, Anisakis simplex, and zoonotic.